The role of obstetricians and neonatologists in childcare in the time of the COVID-19 pandemic - Borowik, Joanna; Kaziród, Karolina; Brodowski, Wojciech; Miturski, Andrzej; Semczuk-Sikora, Anna (Journal of Education, Health and Sport, 2022)
Introduction: The COVID-19 pandemic has caused numerous changes to the healthcare system, including care for the newborns. Aim of the study: The aim of the study was to create a clear set of recommendations used in the care of a newborn during the SARS-CoV-2 pandemic. State of knowledge: Despite the low risk of infection of the newborn in utero or during vaginal delivery, in rare cases there is a possibility of vertical transmission of the SARS-CoV-2 virus. Every newborn baby whose mother has been diagnosed with COVID-19 disease should be screened for infection. Suspected neonates should be isolated from healthy children and kept in quarantine until the test result is obtained. It is essential to constantly monitor your baby’s health and be alert to any possible signs of infection. Medical personnel should ensure adequate protection when handling an infected newborn. A healthy infant whose mother is SARS-Cov-2 positive may be discharged home provided it is looked after by a healthy caregiver. Summary: New patterns of management in maternity and neonatal departments are associated with changes that may have a significant impact on the mother-child relationship. When making decisions aimed at reducing the spread of SARS-CoV-2 infection, it is necessary to seek solutions taking into account the needs of this particular group of patients.